Evaluating diagnostic accuracy of Ovarian instant frozen sections compared to delayed paraffin embedded permanent sections - Hatami, Hossein; Mohsenifar, Zhaleh; Salimi, Amir (Researcher Bulletin of Medical Sciences, 2020)
Introduction: Frozen section is mainly performed to determine malignity, so it is of fundamental importance to evaluate the diagnostic accuracy of frozen sections performed for each group of tissues in order to reduce false diagnoses, unnecessary surgeries and following unwanted complications. This study is conducted to evaluate the diagnostic accuracy of frozen section performed on ovary tissue compared to permanent sections. Materials and Methods: In this retrospective study, we evaluate frozen sections performed at Taleghani hospital pathology department in five years and their results were compared with permanent sections’ results to calculate sensitivity, specificity, negative predictive value and positive predictive value. In cases which results were discordant, we check for probable reasons. Results: 83 species were evaluated from patients with a mean age of 42.9 years; the smallest was 19 and the oldest was 86 years old (Std. dev: 12.84). 75 cases of frozen sections were benign (90.4%) and 8 cases were malignant. 73 cases of permanent sections were benign (88%) and 10 cases were malignant (12%. Sensitivity, specificity, positive predictive value and negative predictive value rates were 66%, 100%, 100% and 96.55% respectively. Conclusions: This study shows the importance of cooperation between pathologist and surgeons that they can prevent unnecessary surgeries. In our study the only cases of discordancy were borderline tumors and the diagnostic accuracy for all other species were perfect.